DECONSTRUCTING ACADEMIC MISCONDUCT: THE MODERATING ROLE OF IT IN A DIAMOND OF FRAUD ANALYSIS - Khresna Bayu Sangka; Kinanthi Suryaningsih; Mi'raj Akbar Pradianto (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to determine how the use of information technology deconstructs and moderates the influence of the diamond fraud perspective on the academic cheating behavior of economics education students.Methodology – This study employs a quantitative research approach, using both descriptive and inferential statistics to analyze relationships among variables thoroughly. Descriptive statistics are used to summarize the data from 183 respondents, highlighting key patterns such as central tendency and data dispersion. At the same time, Moderated Regression Analysis (MRA) and the prerequisite tests were used to provide a clearer understanding of the sample characteristics and lay the groundwork for hypothesis testing.Findings – The results show that the use of information technology does not strengthen or weaken the influence of pressure on academic cheating behavior, the use of information technology does not strengthen or weaken the opportunity for academic cheating behavior, the use of information technology does not strengthen or weaken the influence of rationalization on academic cheating behavior, and the use of information technology does not strengthen or weaken the influence of ability on academic cheating behavior.Contribution – The contribution of this research is for study programs and faculties, as well as lecturers, as evaluation material related to academic cheating actions when completing assignments or exams by establishing strict rules and norms that must be implemented to reduce academic cheating committed by students.